Nuclear IGF1R Interacts with Regulatory Regions of Chromatin to Promote RNA Polymerase II Recruitment and Gene Expression Associated with Advanced Tumor Stage - Aleksic, Tamara; Gray, Nicki; Wu, Xiaoning; Rieunier, Guillaume; Osher, Eliot; Mills, Jack; Verrill, Clare; Bryant, Richard J; Han, Cheng; Hutchinson, Kathryn; Lambert, Adam G; Kumar, Rajeev; et al. (Cancer research (Chicago, Ill.), 2018)
Internalization of ligand-activated type I IGF receptor (IGF1R) is followed by recycling to the plasma membrane, degradation or nuclear translocation. Nuclear IGF1R reportedly associates with clinical response to IGF1R inhibitory drugs, yet its role in the nucleus is poorly characterized. Here, we investigated the significance of nuclear IGF1R in clinical cancers and cell line models. In prostate cancers, IGF1R was predominantly membrane localized in benign glands, while malignant epithelium contained prominent internalized (nuclear/cytoplasmic) IGF1R, and nuclear IGF1R associated significantly with advanced tumor stage. Using ChIP-seq to assess global chromatin occupancy, we identified IGF1R-binding sites at or near transcription start sites of genes including and , most sites coinciding with occupancy by RNA polymerase II (RNAPol2) and histone marks of active enhancers/promoters. IGF1R was inducibly recruited to chromatin, directly binding DNA and interacting with RNAPol2 to upregulate expression of JUN and FAM21, shown to mediate tumor cell survival and IGF-induced migration. IGF1 also enriched RNAPol2 on promoters containing IGF1R-binding sites. These functions were inhibited by IGF1/II-neutralizing antibody xentuzumab (BI 836845), or by blocking receptor internalization. We detected IGF1R on and promoters in fresh prostate cancers that contained abundant nuclear IGF1R, with evidence of correlation between nuclear IGF1R content and JUN expression in malignant prostatic epithelium. Taken together, these data reveal previously unrecognized molecular mechanisms through which IGFs promote tumorigenesis, with implications for therapeutic evaluation of anti-IGF drugs. These findings reveal a noncanonical nuclear role for IGF1R in tumorigenesis, with implications for therapeutic evaluation of IGF inhibitory drugs. .